Дослідження та аналіз конструкції системного блоку ПК - Кузяєв, Д. Р. (My University, 2020)
In this work, the parameters of PC system unit, which is necessary for modeling the process of cooling in PC, were investigated and further analyzed. The following parameters are selected: body type (form factor, size) and material; cooling system; structural elements, fasteners. appearance, design. The difference between housing standards is considered. The analysis revealed that the process of effective functioning depends on competent organization of ventilation process.
Keywords: системний блок ПК; плата; система охолодження